RMP predicts survival and adjuvant TACE response in hepatocellular carcinoma - Zhang, Jian (Oncotarget, 2014)
Adjuvant transcatheter arterial chemoembolization (TACE) protects against hepatocellular carcinoma (HCC) and is associated with reduced disease recurrence and improved outcome after surgery. However, deterioration of liver function after TACE negatively impacts the patient prognosis and limits it use as an option to prolong survival. We analyzed two independent cohorts that included a total of 510 patients with HCC who had undergone tumor resection. Immunohistochemistry assay was used to measure RPB5-mediating protein (RMP) expression and assessed their association with recurrence rate and response to therapy with adjuvant TACE. In patients with HCC, the expression of RMP in tumor is associated with age, gender, tumor size, portal venous invasion, TNM stages, BCLC stages and overall survival. Among patients with high RMP expression, adjuvant TACE after resection was associated with early recurrence. Even in the patients with small tumor size (no more than 5 cm) or no venous invasion, RMP status is associated with response to adjuvant TACE. RMP status in tumors may be a useful marker in estimating prognosis in patients with HCC and in assisting in the selection of patients who are likely to benefit from adjuvant TACE to prevent relapse.